HPLC determination, pharmacokinetics and relative bioavailability of levofloxacin produced by «OZONE», Russia - S. N. Kondratenko; A. K. Starodubtcev; E. A. Senik; O. V. Dralova; S. N. Kudinova (Фармакокинетика и Фармакодинамика)
A simple, specific, sensitive and reproducible good method for quantitative determination of Levofloxacin in plasma using HPLC with UV-spectrophotometric detection. With this technique the pharmacokinetics and relative bioavailability of domestic generic of levofloxacin in 18 healthy volunteers after a single oral dose of 500 mg. Found that the drug being tested, levofloxacin (OOO «Ozone», Russia) is bioequivalent to the reference drugs Tavanic® («Sanofi Winthrop Industry», France).